New CEOs and their collaborators: Divergence and convergence between the strategic leadership constellation and the top management team - Ma, Shenghui; Seidl, David (Strategic management journal, 2018)
Research summary: An important challenge that new CEOs face is establishing a group of immediate collaborators, which we call the "strategic leadership constellation." Drawing on a comparative case study, we show that due to constraints on the CEO to change the top management team (TMT), the composition of the strategic leadership constellation initially tends to differ from that of the TMT: in some cases, it consists of a subgroup of the TMT; in others, it also comprises individuals outside the TMT such as staff members or lower-level managers. We show that the discrepancies between the strategic leadership constellation and the TMT lead to tensions that trigger a process of convergence between these two bodies, particularly as the constraints on TMT change decrease and the CEO's needs evolve. Managerial summary: A major challenge that new CEOs face is establishing a group of close collaborators, which we call the "strategic leadership constellation." Our study shows that due to different constraints on changing the executive team, the composition of the strategic leadership constellation initially tends to differ from that of the executive team: in some cases, it consists of a subgroup of the executive team; in others, it also comprises individuals outside the executive team, such as staff members or lower-level managers. We show that the discrepancies between the strategic leadership constellation and the executive team lead to tensions that trigger a process of convergence between these two bodies, particularly as the constraints on changing the executive team decrease and the CEO's needs evolve.